Identifikasi dan Penentuan Pohon Filogenetik Spodoptera frugiperda Asal Jawa Berdasarkan Analisis Sekuen MtDNA COI - Widarti, Ani; Tauruslina, Enie; Faridah, Idah; Bagariang, Willing; Suyanto, Hadi; Mahmudah, Didah; Susanti, Rista; Maryana, Rosalia; Carwika, Carwika (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2022)
Molecular confirmation of the existence of Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) on Java Island has not been widely reported. This study aimed to identify the armyworm from Java Island molecularly based on DNA mitochondrial cytochrome oxidase I (MtDNA COI). There were six armyworms collected from West Java Province (Cirebon - JWB1, Garut - JWB2), Central Java Province (Wonogiri - JWTH), East Java Province (Gresik - JWTR), DI Yogyakarta Province (Bantul - DIY), and Banten Province (Serang - BNT). The results showed that the fall armyworm originating from Java was verified as Spodoptera frugiperda. There were species variations between them, which had species similarity between regions and countries, namely the species similarity of S. frugiperda Java and West Sumatra, as well as to China, Korea, and India. S. frugiperda from Central Java (JWTH), Banten (BNT), West Java 1 (JWB1), and Yogyakarta (DIY) had species similarity to S. frugiperda from Solok (No. Acc. MW876212.1), West Pasaman (No. Acc. MW876211.1), China (No.Acc. MK591010.1) and Korea (No.Acc. MN427930.1). Meanwhile, S. frugiperda West Java (JWB2) and East Java had species similarity to S. frugiperda from India (No. Acc. MT732476.1), Padang Pariaman (No. Acc. MW876208.1), and Tanah Datar (No. Acc. MW876210.1).